2000
DOI: 10.1007/pl00009108
|View full text |Cite
|
Sign up to set email alerts
|

Design of experiments in the biodegradation of phenol using immobilized Pseudomonas pictorum (NICM-2077) on activated carbon

Abstract: Pseudomonas pictorum (NICM-2077) immobilized on various matrices are used to protect the microbes from confronting shock loads of concentrated phenol. The cells were immobilized in activated carbon and were used in biodegradation of phenol. Biodegradation of phenol using immobilized Activated Carbon matrix played an important role in reducing the toxicity of phenol. The degradation was carried and using the Box-Behnken model and analysis of variance have been applied to the experimental degradation studies. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…Biodegradation of phenol in an aqueous solution is highly dependent on pH of the solution, which affects the surface charge of the absorbent and the degree of ionization (Annadurai et al 2000). Increasing the pH of the media from 6 to 8 at 30 ºC increases the rate of degradation of phenol (Figure 3).…”
Section: Effect Of Phmentioning
confidence: 99%
“…Biodegradation of phenol in an aqueous solution is highly dependent on pH of the solution, which affects the surface charge of the absorbent and the degree of ionization (Annadurai et al 2000). Increasing the pH of the media from 6 to 8 at 30 ºC increases the rate of degradation of phenol (Figure 3).…”
Section: Effect Of Phmentioning
confidence: 99%
“…Bacterial cells maintain an internal osmotic pressure at about 0.85% solution of NaCl. If the environment has a lower osmotic pressure than the cell (hypotonic), water tends to penetrate into the cell, and higher extracellular osmotic pressure (hypertonic) causes the protoplasm to lose water through the partially permeable cell membrane [8,[34][35][36][37]. A hypotonic environment is the normal condition for most of the bacteria and they tend to exit in a distended form, maintaining their shape within the cell wall.…”
Section: Effect Of Sodium Chloridementioning
confidence: 99%
“…Phenol and its derivatives is the basic structural unit in a wide variety of synthetic organic compounds (Annadurai et al, 2000). It is an organic, aromatic compound that occurs naturally in the environment (Prpich and Daugulis, 2005), but is more commonly produced artificially from industrial activities such as petroleum processing, plastic manufacturing, resin production, pesticide production, steel manufacturing and the production of paints and varnish (Mahadevaswamy et al, 1997;Bandyopadhyay et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of techniques involving physical, chemical and biological methods have been used for the removal of phenol from industrial effluents and contaminated The meta-cleavage pathway for the biodegradation of phenol A= Phenol, B= Catechol, C= 2-Hydroxymuconic semialdehyde, D= 2-Hydroxymuconate, E= 2-Oxo-4-enoadipate, F= 2-Oxo-penta-4-enoate, G= Pyruvate, H= Acetaldehyde, I= Acetyl Co A, E1= Monooxygenase phenol hydroxylase, E2=Catechol-2, 3-dioxygenase, E3= Hydrolase, E4= Dehydrogenase, E5= Isomerase, E6= Decarboxylase, E7= Hydrotase, E8= Aldolase waters with bioremediation receiving the most attention due to its environmental friendliness, its, ability to completely mineralize toxic organic compounds and of low-cost (Kobayashi and Rittman, 1982;Prpich and Daugulis, 2005). Microbial degradation of phenol with different initial concentrations ranging from 50-2000 mg/L have been actively studied using shake flask, fluidized-bed reactor, continuous stirred tank bioreactor, multistage bubble column reactor, air-lift fermenter and two phase partitioning bioreactor methods (Bettmann and Rehm, 1984;Sokol, 1988;Annadurai et al, 2000;Reardon et al, 2000;Ruiz-ordaz et al, 2001;Oboirien et al, 2005;Prpich and Daugulis, 2005;Saravanan et al, 2008) and these studies have shown that phenol can be aerobically degraded by wide variety of fungi and bacteria cultures such as Candida tropicalis (Ruiz-ordaz et al, 2001, Chang et al, 1998Ruiz-ordaz et al, 1998); Acinetobacter calcoaceticus (Paller et al, 1995); Alcaligenes eutrophus (Hughes et al, 1984;Leonard and Lindley, 1998); Pseudomonas putida (Hill and Robinson, 1975;Kotturi et al, 1991;Nikakhtari and Hill, 2006); and Burkholderia cepacia G4 (Folsom et al,1990, Solomon et al,1994. In microbial degradation of phenol under aerobic conditions, the degradation is initiated by oxygenation in which the aromatic ring is initially monohydroxylated by a mono oxygenase phenol hydroxylase at a position ortho to the pre-existing hydroxyl group to form catechol.…”
Section: Introductionmentioning
confidence: 99%